Bursectomy versus omentectomy alone for resectable gastric cancer (JCOG1001): a phase 3, open-label, randomised controlled trial. (July 2018) - Kurokawa, Yukinori; Doki, Yuichiro; Mizusawa, Junki; Terashima, Masanori; Katai, Hitoshi; Yoshikawa, Takaki; Kimura, Yutaka; Takiguchi, Shuji; Nishida, Yasunori; Fukushima, Norimasa; Iwasaki, Yoshiaki; Kaji, Masahide; et al.
Summary: Background: The role of bursectomy, in which the peritoneal lining covering the pancreas and the anterior plane of the transverse mesocolon are dissected, has long been controversial for preventing peritoneal metastasis. We investigated the survival benefit of bursectomy in patients with resectable gastric cancer. Methods: This phase 3, open-label, randomised controlled trial was done at 57 hospitals in Japan. Patients aged 20–80 years who had cT3(SS)–cT4a(SE) histologically proven gastric adenocarcinoma with an Eastern Cooperative Oncology Group performance status of 0 or 1 and body-mass index less than 30 kg/m 2 and who did not have distant metastasis or bulky lymph nodes were randomly assigned (1:1) during surgery to receive omentectomy alone (non-bursectomy) or bursectomy. Randomisation was done by telephone or website to the Japan Clinical Oncology Group Data Center and used a minimisation method with a random component to adjust for institution, cT status (T3 vs T4a), and type of gastrectomy (distal vs total). Both groups had total or distal gastrectomy with D2 lymphadenectomy. The primary endpoint was overall survival, analysed in the intention-to-treat population. The study is registered with UMIN-CTR, number UMIN000003688. Findings: Between June 1, 2010, and March 30, 2015, 1503 patients were enrolled based on preoperative inclusion and exclusion criteria. Intraoperative inclusion and exclusion criteria were met in 1204 patients, of which 602 were allocated to the non-bursectomy group and 602 were allocated to the bursectomy group. At the planned second interim analysis on Sept 17, 2016, the JCOG Data and Safety Monitoring Committee independently reviewed the results and recommended their early publication on the basis of futility because overall survival was lower in the bursectomy group than the non-bursectomy group, and because the predictive probability of overall survival being significantly higher in bursectomy than non-bursectomy patients at the final analysis was only 12·7%. 5-year overall survival was 76·7% (95% CI 72·0–80·6) in the non-bursectomy group and 76·9% (72·6–80·7) in the bursectomy group (hazard ratio 1·05, 95% CI 0·81–1·37, one-sided p=0·65). 64 (11%) of 601 in the non-bursectomy group and 77 (13%) of 600 patients in the bursectomy group had grade 3–4 operative morbidity. Pancreatic fistula was significantly more common in the bursectomy group than in the non-bursectomy group (29 [5%] vs 15 [2%]; p=0·032). Six deaths occurred either in hospital or within 1 month of surgery: five in the non-bursectomy group and one in the bursectomy group. Interpretation: Bursectomy did not provide a survival advantage over non-bursectomy. D2 dissection with omentectomy alone should be done as a standard surgery for resectable cT3–T4a gastric cancer. Funding: Japan Agency for Medical Research and Development, the Ministry of Health, Labour and Welfare of Japan, and the National Cancer Centre Research and Development Fund.